A CONDIÇÃO SEMIÓTICA DOS MUROS: análise a partir da psicanálise freudiana no estudo da interpretação dos sonhos - Filgueiras, Tiago Mendes (Revista Estética e Semiótica- RES, Aesthetics and Semiotics Magazine, 2014)
This article takes the Freudian thought on the formation process of dreams and the diverse possibilities of its analysis to a reflection about the symbolic universe in which the wall is inserted. Focussing mainly on the methodology underlying these two processes, the “condensation work” and the “displacement work”, created by Freudto explain how dreams are formed, this text approaches the countless meanings that are incorporated in the wall through to its insertion in many cultures, especially the urban. This defined methodology goes through historical, semiotic and aesthetic perspectives, and focuses on bringing out aspects of the wall that turn it into a much richer element than a simple barrier